Prevalence and ablation of different anatomic locations of atrial tachicardias in the electrophysiology lab of a single large center. (24th May 2021) - Toniolo, M; Rebellato, L; Muser, D; Daleffe, E; Proclemer, A; Facchin, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Focal atrial tachycardias (ATs) can arise from several different anatomic regions both in the right atrium (RA) and left atrium (LA). The prevalence of focal atrial tachycardia is not well known. A European study of young males applying for pilot licenses demonstrated that 0.34% had asymptomatic atrial tachycardia and 0.46% had symptomatic atrial tachycardia1. It is well-recognized that these foci do not occur randomly throughout the atria but tend to cluster at characteristic anatomic locations. However, the distribution of these sites in the total amount of ATs is not well recognized. Purpose: The objective of this study was to determine the prevalence of different anatomic locations of ATs in the electrophysiology lab of a single large center (300 ablations per year) and to verify the site of ablation. Methods: We collected 150 consecutive patients submitted to catheter ablation of ATs between January 2010 to December 2020. Anatomic localization of the atrial focus was performed during tachicardia by analysis of endocardial activation sequence. Results: The distribution of the different anatomic locations is rappresented in the figure. In 134 patients (89%) ATs were localized in the RA. In the RA, these foci mainly occured along the crista terminalis (32%), the perinodal region (22, 6%), the anterior right sided septum, near the foramen ovale (9, 3%), the posterior right-sided septum (8%), the ostium of the coronary sinus (5, 3%), the tricuspid annulus (5, 3%), the superior vena cava (4, 6%), the infero-lateral wall (2, 5%), the right atrial appendage (0, 6%) and the cavotricuspid histhmus (0, 6%). In the LA (11%), foci occur predominantly at the pulmonary vein ostia (5, 2%) and less commonly at the mitral annulus (2, 5%), the left sided septum (0, 6%), the appendage ridge (0, 6%), the roof (0, 6%) and the anterior wall (0, 6%). For each location of AT, the ablation was performed at the earliest activation site, but about the perinodal ATs, the ablation was performed at the non coronary sinus of Valsalva of the aortic root, regardless the earliest activation site, for avoiding to create damages to the atrio-ventricular (AV) conduction system. Conclusions: ATs mainly arise from the RA. Crista terminalis is the most common site but the perinodal region is the second more frequent site. The ablation of ATs from the perinodal region is challenging for the risk of damages to the AV conduction system. The relatively low prevalence of ATs arising from the pulmonary veins could be explained for the likely degeneration of these ATs in atrial fibrillation.